23 The Impact of Parental History of Substance Use on Preadolescent Rewarding Processing in the ABCD Study - Navarro, Gabriella Y; Stinson, Elizabeth Ashley; Sullivan, Ryan; Lisdahl, Krista (Journal of the International Neuropsychological Society, 2023)
Objective:Parental history (PH) of problematic substance use has been identified as a risk factor for adolescent substance use, which can lead to increased use in adulthood. Researchers hypothesize that individuals with PH exhibit premorbid differences in their reward processing, increasing their likelihood of engaging in reward-driven behavior. Studies have shown that preadolescents with PH have greater activation in their putamen and nucleus accumbens (NA); however, most research has only investigated PH of alcohol use (PHA), not PH of drug use (PHD). Additionally, limited research has assessed whether reward processing develops differently among youth with (PH+) to youth without (PH-). The present study utilizes the national, prospective Adolescent Brain Cognitive Development SM (ABCD) Study to examine whether reward anticipation in the nucleus accumbens (NA) differs in preadolescents with and without parental substance use history and whether patterns of reward anticipation change over time during a two-year follow-up period. Further, it will also examine whether PHA and PHD predict similar activation patterns.Participants and Methods:The current sample (N=6,600, Mage = 10.9; range = 9-13.8 years old; 46.7% female) was drawn from the national ABCD Study. To assess reward processing, the Monetary Incentive Delay Task (MID), a fMRI task-based paradigm, was administered at baseline and 2 year follow-up. The primary regions of interest (ROI) were the left and right NA and neutral vs anticipation of large rewards was the selected contrast. The Family History Assessment was used to assess problematic parental alcohol and drug use for both parents, with scores ranging from 0-2, with two indicating that both parents demonstrate problematic use. Three PH contrasts (PH- vs.PH+1, PH-vs.PH+2, & PH+1 vs. PH+2) were created for each group (PHA and PHD) (Martz et al., 2022). Separate linear mixed-effect models with predictors variables (parental contrasts, timepoint, and parental contrasts-by-time-point) and covariates (age, sex, race/ethnicity, income, parental education, parental warmth, parental monitoring, and the random effects of MRI model, family status, and subject) were run to predict reward anticipation.Results:Results indicated that PHA and,not PHD, was predictive of reward anticipation. PHA+1 youth showed greater activation in the l-NA (b= .02827, p= .03) and r-NA (b= .03476, p=.005), compared to PH- youth. Additionally, PHA+1 youth showed greater activation in the r-NA (b=-.07029, p=.008) compared to PHA+2 youth, but not in the l-NA. Those with PHA+2 demonstrated blunted activity in both the l-NA (b= -.07244, p=.02) and right nucleus accumbens (b= -.1091, p=001) when compared to those with PH-. No interactions with time were found.Conclusions:Preadolescents with a PHA+ for both parents had blunted activity in reward anticipation, conferring a unique risk not seen in youth with only one parent with problematic alcohol use, or in youth with a PH of drug use. Future research should attempt to disentangle both genetic and environmental factors that may explain these discrepancies in reward processing, as well as the protective factors that may mitigate it. The current study found no interaction between PHA+ and time, suggesting that during preadolescents, the pattern of reward functioning remains consistent, but future work should assess if this pattern holds up across adolescence